SCOP qui peut ! - Maxime Quijoux (Cahiers d’histoire.)
In the shadow of the 1968s, the 1980s was a period rich in workers' experiences that are still little known. Combining both public authorities and trade unions, this period also marked the affirmation of the “Confédération Générale des SCOP de France” (CGSCOP). Since its institutionalisation at the end of the 19th century, this structure has remained relatively marginal among the organisations representing workers. This article will look back at this little-known but decisive sequence in understanding the social transformation projects of this period. Firstly, we will see, for example, that an interest in workers' cooperation at the end of the 1970s was far from being the prerogative of the left: it constituted an 'ecumenical utopia' that included a number of right-wing political actors, particularly in the dual context of the promotion of the enterprise and industrial crises. Secondly, we will try to understand the effects of the Socialist victory in 1981 on the production cooperative movement. The CGSCOP was not the only one to invest in the cooperative field. It was joined by the CGT, which was looking for a response to the increasing number of company bankruptcies. Finally, we shall see how this all-out appropriation of cooperation gave rise to a multitude of tensions and disillusionment, leading to the rapid marginalisation of a workers' conception of self-management. In short, it was not so much the collective enterprise as a certain form of popular power that closed the cycle of the 1968s.